Tying governments' hands: Why harmonisation of environmental policies may be desirable - Surjinder Johal; Alistair M. Ulph (Fondazione Eni Enrico Mattei (FEEM), 1998)
We consider environmental policy in a federal system where states face purely domestic environmental problems. It is normally argued that in this context, environmental policy is best set at the state level, perhaps because of better local information. To provide a rationale for federal involvement, we use a simple strategic trade model in which if states act non-co-operatively they set laxer environmental policies than if they acted co-operatively ("environmental dumping"). While this provides a possible role for a federal government to co-ordinate environmental policies, it is sometimes argued that a federal government should impose uniform environmental policies across states (harmonisation). It is well known that harmonisation would be inefficient if states differ in important respects, such as environmental damage costs. We showed elsewhere that even if there is asymmetric information, so that damage costs in a state is private information to that state's government, it is better to set environmental policy at the federal level, and that while environmental policies for states with different damages costs will differ less than would be the case with symmetric information, this does not justify harmonisation. Our earlier work assumed welfare maximising governments. In this paper we assume that governments at state and federal level can be influenced by pressure groups. In our model we assume there are two such groups - environmentalists and industrialists. Depending on which group's interests are represented by the government in power a government may give too high or too low a weight to environmental damages relative to its weight in social welfare. As in our earlier work, the true value of environmental damage costs in each state is private information to the state government which comes into power. There is then a choice between allowing governments to set environmental policy using the information they acquire about damage costs, but giving these costs too high or too low a weight (political discretion), or tying governments hands by prescribing policies which maximise welfare, but based on the expected value of damage costs (social pooling). In our model social pooling implies harmonisation. We show that with both political discretion and social pooling it is better to set environmental policy at the federal level. For a wide set of parameter values it will be desirable to tie governments' hands if policy is set at the federal level, but not to do so if it is set at the state level. This may provide an explanation why calls for harmonisation of environmental policies arise when policies are considered at the federal level, but not when they are considered at the state level.
Keywords: F1; H7; Q2; 330; Environmental policy co-ordination; Harmonisation; Asymmetric information; Political economy; Federal/State relations; Umweltpolitik; Wohlfahrtstheorie; Asymmetrische Information; Neue politische Ökonomie; Theorie; Föderalismus